Intangible Capital in France and Germany: Is there a Measurement Issue? - Alberto Nonnis; Felix Roth; Ahmed Bounfour (University of Hamburg, Department of Economics, Senior Lectureship in International Economics, 2024)
In this article, we highlight important differences in capital investment and capital stock in intangible assets between France and Germany, which we attribute to potential measurement issues between the two countries. Using data from the latest EUKLEMS/INTANProd release for the period between 1995 and 2020, we identify investment in software and databases, along with investment in organizational capital, as key drivers of these differences. Investment in software appears to be four times higher in France than in Germany, while organizational capital is about two and a half times larger in France. Given the comparable economic growth patterns of these two countries over recent decades, we believe these measurement discrepancies could have significant implications for understanding both past growth trends and future growth perspectives.
Keywords: 330; Intangible capital; Labour Productivity; Germany; France; EU